Health education of clean and healthy life behavior among mother in Kasiguncu Village, Poso - Firaningsih, Dwi; Sitorus, Sony Bernike Magdalena; Nurfatimah, Nurfatimah; Longgupa, Lisda Widianti; Ramadhan, Kadar (Universitas Muhammadiyah Magelang, 2021)
Clean and Healthy Living Behavior is a behavior when someone applies hygiene behavior in their daily life by paying attention to their level of health. The purpose of this activity is to increase mother's knowledge about clean and healthy living behavior. This activity was carried out in Kasiguncu Village. The target of this activity was mothers who come to the posyandu. In this activity the number of participants was limited to 9 people, because the counseling was carried out by implementing the Covid-19 pandemic health protocol. The parties involved in this activity are the coordinating midwife and community health program holder at the Mapane Health Center, as well as the Kasiguncu Village midwife. The method in this activity was doing a pretest, followed by counseling using leaflets, and finally filling out the posttest. The results of this activity obtained an increase in mother's knowledge. The average knowledge before counseling was 62.22 and the average after counseling increased to 85.56. We suggest to health workers/services and health cadres to provide more counseling or health education at each posyandu so that it has an impact on increasing clean and healthy living behavior in their environment to prevent various diseases.